The work of being a wallflower: The peripheral politics of male sentimentality - Carrillo-Vincent, Matthew (ProQuest Dissertations & Theses, 2013)
One need not strain to find examples of male sentimentality in contemporary US popular culture: From frequent news stories on "Weeper of the House" John Boehner, to the success of Judd Apatow's poignant "bromance" movies, to last year's film adaptation of Stephen Chbosky's celebrated adolescent novel, The Perks of Being a Wallflower (1999), the man of feeling seems more present and popular than ever. With an unsettling display of excessive emotion emanating from the male body, each iteration provokes in viewers, listeners, and cultural critics any one of several disparate responses: Whether committed to the transgressive potential of a male who feels different because he offers vulnerability where others offer hardened restraint, or whether insistent in the claim that these texts simply add to what Gail Bederman would call the "remaking" of a continually complex normative subject, we find in the man of feeling an ambivalent subject for the public sphere. The initial question for readers, listeners, or viewers is often a simple one: is male sentimentality transformative and progressive, or is it pathetic and self-serving? But the presumption that we must answer one way or another belies the historical and cultural complexity of the man of feeling, and merely reinforces a kind of political approach to reading that simply replicates our own attitudes and relation to normativity and its privileges. This dissertation—under the impulse of recent work in queer theory and affect to reach closer to, rather than further from, normativity—takes up the counterintuitive position that we might draw this unlikely subject of the wallflower out from the sidelines and use him to interrogate normativity not from outside, but rather beside, its unsteady borders. It asks a central question—What does it mean for a critique of normativity to come from the normative subject?—and argues that the "peripheral" reading of normativity he helps enable might serve to render the logics of normativity in different ways than we can with more traditionally oppositional forms of critique.